Anti-Desmocollin Autoantibodies in Autoimmune Blistering Diseases - Bosch-Amate, Xavier; Iranzo, Pilar; Ivars, Marta; Mascaró Galy, José Manuel; España, Agustín (Frontiers in Immunology, 2021)
The presence of anti-desmocollin (Dsc) antibodies is rarely described in autoimmune blistering diseases patients. Moreover, several clinical phenotypes of pemphigus may be associated with these antibodies. In this review we analyse clinicopathological, immunologic and outcome features of anti-Dsc autoimmune blistering diseases patients, to improve their diagnosis and management. We conducted a systematic search of PubMed and Embase (1990-present) for studies reporting cases of autoimmune blistering diseases with anti-Dsc antibodies. We classified the selected patients as patients with exclusively anti-Dsc autoantibodies, and patients with anti-Dsc and other autoantibodies. Of 92 cases with anti-Dsc autoantibodies included, 37 (40%) had exclusively these antibodies. Only 17% of patients presented with the typical clinicopathological phenotype of pemphigus vulgaris or pemphigus foliaceous. Mucosal involvement was seen in approximately half of the patients. Up to 18% of cases were associated with neoplasms. Acantholysis was described in 53% of cases with histopathological information. Treatments and outcomes vary in the different clinical phenotypes. The presence of anti-Dsc antibodies must be suspected mainly in those patients with either atypical pemphigus, in special with clinical pustules, or in cases showing intraepithelial or dermal neutrophilic/eosinophilic infiltrate on histological examination and dual pattern by direct immunofluorescence examination.